2009
DOI: 10.1111/j.1399-5448.2009.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial HTN in children with T1DM-frequent and not easy to diagnose

Abstract: Children with T1DM often suffer from nocturnal, white coat- and masked HTN, which can not be assessed and predicted by the OBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 31 publications
2
19
1
1
Order By: Relevance
“…67 Other pediatric studies have reported the prevalence of WCH to be in the range of 22% to 32%. 68 Of note, Sorof et al 69 have suggested that the use of ABPM to rule out WCH should be limited to patients with borderline or mild clinical hypertension, because patients with higher office BP levels are more likely to be truly hypertensive.…”
Section: Usefulness Of Abpm To Classify Bpmentioning
confidence: 99%
“…67 Other pediatric studies have reported the prevalence of WCH to be in the range of 22% to 32%. 68 Of note, Sorof et al 69 have suggested that the use of ABPM to rule out WCH should be limited to patients with borderline or mild clinical hypertension, because patients with higher office BP levels are more likely to be truly hypertensive.…”
Section: Usefulness Of Abpm To Classify Bpmentioning
confidence: 99%
“…ABPM is particularly useful in children with whitecoat and masked HTN as these conditions are not uncommon [88,89] and would not be diagnosed by the office BP. Masked HTN in children and adolescents is associated with a similar risk of end-organ damage as in established HTN [90,91].…”
Section: Abpmmentioning
confidence: 99%
“…Even white-coat HTN may lead to significant end-organ damage [92,93] and therefore represent a prehypertensive state [92]. The prevalence of both masked and white-coat HTN is not negligible, especially in children with chronic conditions, such as chronic kidney disease [94] and diabetes mellitus type 1 [89]. This further underlines the importance of ABPM in children.…”
Section: Abpmmentioning
confidence: 99%
“…The association of elevated BP and abnormal circadian BP pattern with early markers of kidney damage suggests the involvement of both renal mechanisms and central regulation of arterial pressure [102][103][104][105]. The metabolic disorders resulting from chronic hyperglycaemia leading to atherosclerosis and increased arterial stiffness are also involved in the development of hypertension in diabetic patients [106][107][108][109].…”
Section: Pathogenesis Of Hypertension In Children With Diabetesmentioning
confidence: 99%